Internal Maxillary to Middle Cerebral Artery Bypass Using an Anterior Tibial Artery Graft, Performed Using a 3-Dimensional Exoscope: 2-Dimensional Operative Video. Issue 2 (7th December 2019) - Patel, Nitesh V; Ligas, Barbara; Gandhi, Shashank; Ellis, Jason; Ortiz, Rafael; Costantino, Peter; Qato, Khalil; Langer, David J
Abstract: Fusiform aneurysms remain challenging entities to treat, as maintenance of flow and prevention of branch occlusion are concerns. Use of endovascular stents may risk nearby branch occlusion. We present a 31-yr-old male with a prior subarachnoid hemorrhage from a left middle cerebral artery (MCA) M1 aneurysm. Informed consent for use of the operative video and information was obtained from the patient. Initially, open clipping was performed with noted residual because of risk of nearby branches. On angiography, a growing fusiform segment distal to the initial aneurysm was noted. The patient was referred to our institution for this finding, and a multidisciplinary team reviewed the case. Endovascular treatment was felt to be risky, as stenting could jail nearby MCA branches. Clipping would also risk occlusion because of scaring from previous hemorrhage. Sufficient flow would be needed, and because the ipsilateral superficial temporal artery was sacrificed in the initial craniotomy, the internal maxillary artery (IMAX) was chosen as the bypass source. A cerebrovascular neurosurgeon, skull base otolaryngologist, and vascular surgeon worked together to perform a left-side IMAX to MCA bypass using an anterior tibial artery graft under 3-dimensional exoscopic visualization. Specifically, a 9-0 nylon suture on a BV-130 needle along with straight and tying forceps were used along with heparinized saline. The bypass was noted to be of robust flow, and the patient did very well on postoperative follow-up. The utilization of an anterior tibial artery graft, IMAX exposure, and corresponding bypass provides educational value, as there are only a limited number of videos on this topic.